Improper Light Curing of Bulkfill Composite Drives Surface Changes and Increases S. mutans Biofilm Growth as a Pathway for Higher Risk of Recurrent Caries around Restorations - Haifa Maktabi; Maria Salem Ibrahim; Abdulrahman A. Balhaddad; Qoot Alkhubaizi; Isadora Martini Garcia; Fabrício Mezzomo Collares; Howard Strassler; Ana Paula P. Fugolin; Carmem S. Pfeifer; Mary Anne S. Melo (MDPI AG, 2021)
How dentists cure a resin-based material has deleterious effects on the material's properties and its interaction with surrounding dental tissues. Biofilm accumulation has been implicated in the pathogenesis of carious lesions around dental restorations, with its composition manifesting expressed dysbiosis in patients suffering from dental caries. To evaluate the influence of varying radiant exposure on the degree of conversion (DC%), Streptococcus mutans biofilm growth, and surface roughness of bulk-fill composites under different light-curing conditions. Two light-curing units (LCU) at 600 and 1000 mW/cm2 were used to simulate curing conditions with different angulations (∢20° and ∢35°) or 2 mm-distance displacements of the LCU tip. The radiant exposure (RE) was assessed, and the composites were analyzed for DC%. Biofilm formation was induced over the bulk-fill composites and analyzed via colony-forming units counting and scanning electron microscopy (SEM). The surface roughness was analyzed via a profilometer and SEM after biofilm formation. Curing conditions with different angulation or displacement decreased RE compared to the "optimal condition". The moderately (∢35°) angulated LCU tip and low (600 mW/cm2) radiant emittance significantly reduced the DC% (p < 0.05). The difference in DC% between the top and bottom of the composites ranged from 8 to 11% for 600 mW/cm2 and 10 to 20% for 1000 mW/cm2. Greater S. mutans biofilm and surface changes were found in composites with non-optimal RE delivery (e.g., tip displacement and angulation) (p < 0.05). Inadequate polymerization of bulk-fill composites was associated with more biofilm accumulation and surface topography changes. Overall, non-optimally performed curing procedures reduced the amount of delivered RE, which led to low DC%, more biofilm formation, and higher surface roughness. The improper light-curing of bulk-fill composites compromises their physicochemical and biological properties, which could lead to inferior clinical performance and reduced restorative treatments' longevity.